2004
DOI: 10.1111/j.1532-5415.2004.52352.x
|View full text |Cite
|
Sign up to set email alerts
|

Site of Death in the Hospital Versus Nursing Home of Medicare Skilled Nursing Facility Residents Admitted Under Medicare's Part A Benefit

Abstract: Patient and facility characteristics predict site of death of Medicare NH patients, but in-hospital death rather than NH death varies geographically and is associated with higher daily Medicare payment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 27 publications
3
55
2
Order By: Relevance
“…In the present study, only the presence of an adjacent affiliated hospital was consistent with the findings of previous studies (15,16,25,26). These studies showed that facility determinants of dying in nursing homes were the existence of a basic policy for EOL care, a physician based in a home care supporting clinic, location in a rural region, being adjacent to an affiliated hospital, being government-owned, location in regions with more nursing home beds, and location in regions with fewer hospital beds.…”
Section: Comparison With Other Studiessupporting
confidence: 82%
“…In the present study, only the presence of an adjacent affiliated hospital was consistent with the findings of previous studies (15,16,25,26). These studies showed that facility determinants of dying in nursing homes were the existence of a basic policy for EOL care, a physician based in a home care supporting clinic, location in a rural region, being adjacent to an affiliated hospital, being government-owned, location in regions with more nursing home beds, and location in regions with fewer hospital beds.…”
Section: Comparison With Other Studiessupporting
confidence: 82%
“…The variables chosen were determined to be pertinent based on the literature [12,[16][17][18][19]24,25] and the authors' own clinical experiences. All records from the nursing home were reviewed by the first author (Takezako) to obtain information in the following domains: demography, the family decision-maker, health condition, resident and family preference for nursing home end-of-life care, presence of a full-time physician, and admission after LTCI.…”
Section: Variablesmentioning
confidence: 99%
“…According to reports [16][17][18][19] for the United States, "advanced directives" was one of the most significant factors related to nursing home death. In Japan, however, neither "advanced directives," including a "living will," nor the attorney system for medical decisions are legally binding [20].…”
Section: Introductionmentioning
confidence: 99%
“…GAO 2000;Huskamp et al 2001) or local area data (Travis et al 2002;Robinson et al 2002;Chen et al 2003) to examine length of hospice service use. Generalizing the results from local or Medicare data to the entire U.S. hospice population can be misleading due to geographical variations (Levy, Fish, and Kramer 2004) and a finding by the 2000 National Home and Hospice Care Survey (NHHCS) (Haupt 2003), revealing that only 79% of discharged hospice patients had Medicare as their primary payment source. Moreover, although the NHHCSs are nationally representative surveys of home health and hospice agencies and their current and discharged patients (Haupt 2003), studies that have used the NHHCS data for estimating length of hospice service use only examined discharged patient data (Kutner, Blake, and Meyer 2002;Haupt 2003).…”
mentioning
confidence: 99%